1990
DOI: 10.1002/ange.19901020613
|View full text |Cite
|
Sign up to set email alerts
|

17O‐NMR‐Spektroskopie von Benzoylverbindungen YC6H4 COX: Empfindlichkeit auf Substituenteneinflüsse als Maß für den Elektronenmangel an der Carbonylgruppe

Abstract: Entgegen einer weit verbreiteten Meinung ist die 13C‐NMR‐Spektroskopie nicht zur Ermittlung von Elektronendichte am Carbonyl‐C‐Atom geeignet. Durch Messung der 17O‐chemischen Verschiebung bei aromatischen Carbonylverbindungen Y‐C6H4‐COX, X = CF3, H, CH3, CO2R, Br, Cl, F, OCOAryl, SR, OR, NH2, OH, O⊖, konnten jedoch verläßliche Aussagen über die Elektrophilie des Carbonyl‐C‐Atoms gemacht werden. Es ist beruhigend, daß die Ergebnisse in Einklang mit klassischen chemischen Regeln sind. Vieles spricht dafür, der 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[13,14] It was found that in methyl benzoates reaction series an introduction of electron-attracting substituents causes deshielding and electron-donating substituents shielding of the carbonyl and methoxy O atoms. [14][15][16] It has been shown [26][27][28][29] that in substituted carbonyl derivatives, Y-C 6 H 4 CO-X, RCO-X, the shielding of the carbonyl oxygen is increased and the sensitivity of the Y substituent is diminished with an increase in the electron-donating power of the X group.…”
Section: The Values Of δ(mentioning
confidence: 99%
“…[13,14] It was found that in methyl benzoates reaction series an introduction of electron-attracting substituents causes deshielding and electron-donating substituents shielding of the carbonyl and methoxy O atoms. [14][15][16] It has been shown [26][27][28][29] that in substituted carbonyl derivatives, Y-C 6 H 4 CO-X, RCO-X, the shielding of the carbonyl oxygen is increased and the sensitivity of the Y substituent is diminished with an increase in the electron-donating power of the X group.…”
Section: The Values Of δ(mentioning
confidence: 99%
“…On the scale of carbonyl electrophilicities, measured by 17 O-NMR spectroscopy [ 29 ], the presence of halogen atoms α- to the carbonyl group decreases the electron density around the oxygen atom ( Table 3 ) [ 29 , 30 ].…”
Section: Molecular Structures and Spectral Propertiesmentioning
confidence: 99%
“…Both observations contrast with acet~phenones'*~ and point to the absence of resonance interaction between the aryl and the phosphoryl groups. Conclusive evidence shows that, in general, monosubstituted phosphinates such as ArHP(0)OR' (2) do not exist as the ArP(0H)OR' tautomers.' l b , I 3 In accord with this, our compounds show a strong P-H couplang (J = 550 Hz) and an IR signal at ca 2350 cm-', typical for P-H." Superficially, the formula of the phosphinate ester group P(=O)OR could be compared with that of a carboxylic ester, C(=O)OR.…”
Section: Introductionmentioning
confidence: 99%